2005
DOI: 10.2303/jecho.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Measurements of Left Atrial Geometry in Patients With Normalized or Restrictive Mitral Flow Velocity Pattern

Abstract: Background. Restrictive or pseudonormalized mitral flow velocity pattern (MFVP) is observed not only in patients with heart failure but also in patients with severe mitral regurgitation (MR). It is important to assess the restrictive MFVP which is primarily due to functional deterioration of the left ventricle or due to MR in individual patients. We hypothesized that left atrial (LA) geometry may be used to estimate restrictive MFVP due to heart failure or MR.Methods. In addition to MFVP and LA chamber size, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The high prevalence of severe diastolic dysfunction and the “elongated” geometry of the left atrium in cardiomyopathy patients suggested a major role of LV filling pattern on LA properties in this group of patients [14]. In order to test this assumption, our 45 cardiomyopathy patients (regardless of etiology) were divided into two groups according to the presence or absence of severe diastolic dysfunction (RFP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of severe diastolic dysfunction and the “elongated” geometry of the left atrium in cardiomyopathy patients suggested a major role of LV filling pattern on LA properties in this group of patients [14]. In order to test this assumption, our 45 cardiomyopathy patients (regardless of etiology) were divided into two groups according to the presence or absence of severe diastolic dysfunction (RFP).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). We used left atrial eccentricity index (LAEi = {2 × D2} / {D1 + D3}) to assess the changes in the LA shape [14] .…”
Section: Methodsmentioning
confidence: 99%
“…LAVi > 40 ml/m 2 is better than LA diameter in predicting AF, death and or mitral valve replacement 9 . Chronic pressure overload may cause an active atrial remodeling, while chronic volume overload may cause a passive atrial remodeling with two different shapes that can be discriminated by LA eccentricity index (LAEi) 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 Chronic pressure overload may cause an active atrial remodeling, while chronic volume overload may cause a passive atrial remodeling with two different shapes that can be discriminated by LA eccentricity index (LAEi). 10 We hypothesized that LA shape described by LAEi may have a better predictive value for the adverse cardiovascular outcome. The goal of our study was to evaluate the relationship between LV diastolic function, MR, LAVi, and LAEi in a cross-sectional study with a population of 5,450 consecutive patients followed in our heart station with echocardiographic examination.…”
Section: Introductionmentioning
confidence: 99%
“…1). A few studies [5][6][7] have demonstrated clinical characteristics of LA dilation evaluated by LAV in patients with normal LAD, but the prognostic implications of the LA dilation have not been investigated. This study was designed to evaluate clinical characteristics and prognosis of LA dilation evaluated by LAV in patients with normal LAD.…”
Section: Introductionmentioning
confidence: 99%